Pengaruh Kemampuan Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan PT. Semen Tonasa Kabupaten Pangkep - Nurhaedah Nurhaedah; Sukmawati Mardjuni; H.M Yusuf Saleh (Universitas Muhammadiyah Gorontalo, 2018)
The purpose of this research is to know the magritude of the influence of the working ability and motivation work towards job satifaction and performance of employees. As well as to know the influence of job sansfaction of the employess en performance. The population in this study as many 232 employees, determining the number of sampel using sloving formula with a sample of 70 employees. The sampel using purpose sampling technique, the study analyzed by Structural Equation Modeling (SEM) with the help of software Smart PLS 2 basaed variance.From the result of the regression in obtai n(1) the result and research shows that the positive effect of work ability and significantly to job satisfaction. (2) the result of the analysis of the influence of work on perpormance capabilities of employees shows there is significant and positive influence amongst (3) he working the analysisand the research shows there is a positive and significant influance between the motivation of working towards job satisfaction the thirtd hypothesis as proven the result of (4) the analysis on the research indicates there is a positive and significant influence between the working motivation afects so (9) this hypotesis proved the result on the analysis the research indicates there is a positive and significant influence between the job satisfaction on performance. Tujuan penelitian ini adalah untuk mengetahui besarnya pengaruh kemampuan kerja dan motivasi kerja terhadap kepuasan kerja dan kinerja karyawan, serta untuk mengetahui pengaruh kepuasan kerja terhadap kinerja karyawan. Populasi dalam penelitian ini adalah karyawan dan karyawati pada PT. Semen Tonasa di Kabupaten Pangkep Divisi Sumber Daya Manusia yasebanyak 232 karyawan, penentuan jumlah sampel menggunakan rumus slovin dengan jumlah 70 karyawan. Penentuan sampel menggunakan teknik purposive sampling, penelitian ini dianalisis melalui Structural Equation Modeling (SEM) dengan bantuan software Smart PLS 2 berbasis varians. Dari hasil analisis dan penelitian menunjukkan bahwa (1) kemampuan kerja berpengaruh positif dan signifikan terhadap kepuasan kerja. (2) Kemampuan kerja berpengaruh positif dan signifikan terhadap kinerja karyawan. (3) Motivasi kerja berpengaruh positif dan signifikan terhadap kepuasan kerja. (4) Motivasi kerja berpengaruh positif dan signifikan terhadap kinerja karyawan. (5) Kepuasan kerja berpengaruh positif dan signifikan terhadap kinerja karyawan pada PT. Semen Tonasa di Kabupaten Pangkep